IMPROVING PHYSICAL EDUCATION OF CHILDREN VIA TEACHING THEM TO SWIM FROM INFANCY - Khamraeva, Zukhro (Innovative Development in Educational Activities, 2023)
The main form of organizing and conducting swimming lessons is a group lesson, which embodies the entire educational process. The task, content and direction of each lesson are determined based on the tasks and educational material set before the course, as well as the knowledge and skills of the participants acquired in the previous lessons.